Impact of Perceived Academic Stress and Depression on Self Efficacy Beliefs among University Students during Online Learning in Peninsula, Malaysia - Mutiu Salami; Rahmattullah Khan; Muhammed Yusuf; Asma Perveen; Mohammed Y.M. Mai (International Journal of Social Learning (IJSL), 2021)
Due to the COVID-19 pandemic, a new challenge has developed specifically among students faced with online learning. The challenge that arises from this type of learning is that the students faced some uncertainties and negative emotional states. This study examined the impact of perceived academic stress and depression on self-efficacy beliefs among university students studying online. One hundred twenty-three participants from two public Universities in Peninsula Malaysia participated through an online google form, which consists of three instruments which are Perception of Academic Stress Scale (PASS), General Self-efficacy (GSE), as well as Depression, Anxiety and Stress Scale (DASS). Findings from Pearson correlation revealed a low negative correlation between general self-efficacy and stress (r = -.269, p < 0.01). On the other hand, the result of a simple linear regression between self-efficacy and perceived academic stress was significant with B = -2.30, p < 0.05. Students with higher levels of academic stress tend to experience depressive symptoms, while self-efficacy was a predictor of perceived academic stress. Considering the current unpredictable pandemic situation, with support from school psychologists and counselors, students are expected to heighten their cognitive drives and beliefs, including the motivation to overcome the challenges inherent in online learning.